The Lifestyle and Health Effects of Obese People - Pandey, Naranath (Madhyabindu Journal, 2023)
Obesity is a complex disease involving an excessive amount of body fat and excessive overweight. In this context, this study aimed to identify the lifestyle and health effects of obese people in Kawasoti Nawalpur. Using a convenient survey method, the researcher examined the association between lifestyle and effects in a sample of 170 respondents. Out of the total 170 respondents, 38 respondents (22.35%) were overweight or obese. After analyzing the data, the researcher found the main cause of obesity in obese people are; eating too much food (71.05%), do not do physical exercises (86.84%), eating junk, and fast food regularly (57.89%), and living a sedentary lifestyle (92.1%). The effects of obesity on obese people are; multiple joint pains (44.73%), having trouble working (63.16%), and high blood pressure (39.48%). The researcher concluded that there is a major problem of obesity and its effects in the community because of the sedentary lifestyle and lack of physical exercise among people. It is recommended to change the lifestyle (eating habits and exercise patterns) and lose weight gradually.